The effect of far-infrared emitting sheets on sleep. (27th July 2018) - McCall, William Vaughn; Letton, Alan; Lundeen, Jordan; Case, Doug; Cidral-Filho, Francisco J.
Abstract : Purpose: The application of far-infrared energy to skin is expected to lead to vasodilatation of the skin surface, consequently warming the skin, and promoting sleep induction. The purpose of this paper was to test whether bedsheets impregnated with bioceramic far-infrared technology would improve the perception of sleep in a sample of healthy adults. Design/methodology/approach: Twenty-nine adults consented to participate, randomizing 17 to the far-infrared bedsheets and 12 to the control bedsheets. Two of the control participants dropped out prior to randomization and prior to completing any assessments and therefore are excluded from the analyses. After baseline assessment, participants slept on their randomly assigned sheets for five weeks, followed by a one week "wash out". Insomnia symptoms were assessed with the Insomnia Severity Index, depression symptoms with the Patient Health Questionnaire, "vigor" and "fatigue" with the Profile of Mood States, and napping behavior with daily sleep diaries. Findings: During the period of randomization, the participants on the far-infrared sheets reported fewer insomnia symptoms and less napping. This advantage was lost during the wash out period. Originality/value: Far-infrared technology produces benefits on reported sleep in healthy normal adults.